Loneliness during the COVID-19 Pandemic in Patients with Burning Mouth Syndrome: A Multicentric Case-Control Italian Study - Adamo, Daniela; Ottaviani, Giulia; Canfora, Federica; Leuci, Stefania; Coppola, Noemi; Pecoraro, Giuseppe; Rupel, Katia; Preda, Magdalena Theodora Bogdan; Vello, Veronica; Albert, Umberto; Gobbo, Margherita; Guarda-Nardini, Luca; et al. (Depression and Anxiety, 2023)
Background. Lockdown restrictions during the COVID-19 pandemic exerted a strong impact on people’s quality of life and increased loneliness. This study evaluates the effect of the pandemic on loneliness in patients with burning mouth syndrome (BMS) compared with the general population. Methods. 100 BMS patients versus 100 healthy controls (HC) were recruited in five Italian centers. The 12-Item General Health Questionnaire (GHQ-12), the Depression Anxiety Stress Scales-21 (DASS-21), the Insomnia Severity Index (ISI), the short-form UCLA Loneliness Scale-8 (ULS-8), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Suicidal Ideation Attribute Scale (SIDAS) were administered. Results. BMS patients and HC showed high scores (16 [14-20.25] and 16 [14-18]) in the ULS-8. Statistically significant differences have been found considering the BMS patients lived with fewer relatives during the lockdown compared with the HC (2 [2-3] and 3 [2-4]; p: 0.012) with a lower level of satisfaction in relationships with relatives (4 [1.75-5] and 5 [4-5]; p<0.001) and also in the DASS-21 total scores between the BMS patients and HC (16 [10-24.2] and 10 [4-17]; p<0.001). The multivariate logistic regression revealed that age, education, DASS-21, and MSPSS were the most predictive variables and could explain 34.68% of the variance in the ULS-8 score (p<0.001) in the BMS group. However, only the DASS-21 was significant in the HC group, explaining 10.11% of the variance of the ULS-8 (p: 0.033). Conclusions. Both the patients and controls experienced deep loneliness during the pandemic. However, in the BMS group, loneliness was significantly correlated with age, a higher level of education and stress, and a lower level of satisfaction in relationships with relatives and social support perceived compared with the controls.